AUTOLOGOUS STEM CELL TRANSPLANTATION AND IMMUNOMODULATION IN AMYOTROPHIC LATERAL SCLEROSIS - AyllÃ³n Ãlvarez, David Uriel; Neri Calixto, Mariana; Aparicio AlbarrÃ¡n, CÃ©sar Humberto; Mendieta ZerÃ³n, Hugo (MNJ (Malang Neurology Journal), 2021)
ABSTRACTBackground: Amyotrophic lateral sclerosis (ALS) is a rare chronic degenerative disease. The only approved treatment, Riluzole, is not available and is not economically affordable for most patients.Objective: To report here a case of a pregnant woman 27 years of age with ALS, confirmed through electromyography. After spontaneous abortion and 88 days without clinical improvement and dependent on mechanical ventilation, treatment with autologous stem cell transplantation and immunomodulation was decided upon for the patient.Methods: The patient received a daily subcutaneous (s.c.) dose of 300 Î¼g human Granulocyte-Colony stimulating factor for a period of 3 days. Peripheral blood mononuclear cells were isolated by leukapheresis. These cells were self-transplanted to the patient 5 cc via lumbar puncture and 5 cc intravenously (i.v.). The immunomodulation treatment was based on the surface-fixation method.Results: The patient remained hospitalized for an additional 249 days, at which time when she was contrareferred to a secondary-level health institution.Conclusion: A treatment scheme combining ASCT (Autologous Stem Cell Transplantation) and immunomodulation, based on the surface-fixation method, could be an option to get a large period of no progression stage in ALS.